Effectiveness Of Family Mart Advertising Through Instagram With Aida Model (@Familymartid) - Gusty Mutiara Medina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Along with the rapid development of digitalization, it is often used by many parties such as business people, this is very important to facilitate the marketing activities of a business. Technology that is often used in marketing, especially in the field of promotion, is Instagram social media. One of the businesses that use Instagram as a promotional media is “Family Mart”, a modern pilot store with a new retail concept and format, namely Convenience Store. This study aims to determine the level of effectiveness of Family Mart advertising through Instagram Social Media @familymartid with the AIDA Model approach. This research is a type of quantitative research with a survey method through filling out a Google Form questionnaire. The sampling method in this study uses non-probablity sampling, using purposive sampling technique. The analysis techniques used in this research are descriptive analysis, simple tabulation analysis, and average scores. The results of this study found that the Attention dimension seen from the measurement of the criterion score is included in the “Good” category and based on the measurement of the average score of 2.57 including the interval level “Effective”. Interest seen from the measurement of the criteria score is included in the “Good” category and based on the measurement of the average score of 2.55 is included in the “Effective” interval level. Desire seen from the measurement of the criterion score is included in the very good category and based on the measurement of the average score of 2.72 is included in the interval level “Effective”. Action seen from the measurement of the criterion score is included in the very “Good” category and based on the measurement of the average score of 2.64 including the interval level “Effective”. Of the four AIDA dimensions, namely Attention, Interest, Desire, and Action, the results of the measurement of the criterion score are included in the “Good” and the measurement of the average score is included in the “Effective” criteria. Of the four dimensions, the highest effectiveness value is Attention, second Interest, third Desire, and fourth Action.